Development and testing of a 200 kW tube bundle moving packed bed electrical heating device and test facility. (April 2023) - Yu, Yupu; Nie, Fuliang; Bai, Fengwu; Liu, Hong; Wang, Zhifeng
Abstract: The solid particle is a promising heat storage media with an allowable temperature usually higher than 800°C. The surplus electricity from renewable energy power generation can be stored in solid particles as the form of thermal energy. However, heating treatment of solid particles remains a difficulty in industry, especially at the level of 800°C. In the current work, a design method for the industrial device of heating moving packed beds is proposed. The flow structure is firstly designed as a bundle of tubes with a parallel connection based on the hydrodynamic behaviors of the moving packed bed. The dimensions of the structure are determined according to the thermodynamic behaviors of the moving packed bed. A test facility with a rated power of 200 kW was manufactured and tested for the validation of the proposed design method. The moving packed bed is heated from 294 °C to 780°C after circulated for four times in the heating device. The errors between the test results and the design points are <10%. The proposed design method can be further applied to the design of multi-megawatt moving packed bed heating devices.